Islamic Education Philanthropy: Ideology and Mission of Pesantren - Isna Nurul Inayati; Khoiriyah Khoiriyah; Abd Wahid (STAI Syaichona Moh. Cholil Bangkalan, 2024)
Abstract: Philanthropy has an important role in developing society in Indonesia, and Islamic educational institutions, in this case Islamic boarding schools, actively participate in implementing philanthropy for the welfare of social life and society. This research aims to examine the essential values, forms of programs and ideology used at the Dalwa Pasuruan Islamic boarding school in implementing philanthropy. The paradigm practiced in this research is postpositivistic with a case study method. The instruments that will be used in this research include: In-depth interviews, active observation and documentation. The data analysis uses the analysis steps described by Robert K. Yin, namely: compiling (collecting data), disassembling (deconstruction), reassembling (recombining), interpreting (interpretation), concluding (conclusion). Meanwhile, to validate the accuracy of the data using triangulation techniques. The results of this research show: first, the essential values of philanthropy in Islamic education used at the Dalwa Islamic boarding school originate from religious texts and humanitarian calls. Second, there are three forms of philanthropic programs in Islamic education implemented at the Dalwa Islamic boarding school, namely philanthropy for students, community, teachers and Asatidz. Third, the ideology that is the basis for constructing Islamic education philanthropy at the Dalwa Islamic boarding school is a scientific hybrid: á¸¥aá¸ramiyah and makiyah as well as a philanthropic ideology that leads to unaffiliation with Islamic organizations. Keywords: Philanthropy, Islamic Education, Islamic Boarding School Abstrak: Filantropi memiliki peran penting dalam membangun masyarakat di Indonesia, dan lembaga pendidikan islam dalam hal ini pesantren turut berpartisipasi aktif dalam implementasi filantropi demi kesejahteraan kehidupan sosial dan masyarakat. Penelitian ini bertujuan untuk mengkaji nilai-nilai esensial, bentuk program-program dan idiologi yang digunakan di pesantren dalwa pasuruan dalam menerapkan filantropi. Paradigma yang dipraktikkan dalam penelitian ini adalah postpositivistik dengan metode studi kasus. Instrumen yang akan digunakan dalam penelitian ini meliputi: Wawancara mendalam (Indepth Interview), Observasi aktif dan Dokumentasi. Adapun analisis data menggunakan langkah-langkah analisis yang dijelaskan oleh Robert K. Yin, yaitu: compiling (mengumpulkan data), disassembling (dekonstruksi), reassembling (penggabungan kembali), interpreting (penafsiran), concluding (penyimpulan). Sedangkan untuk memvalidasi keakuratan data menggunakan teknik triangulasi. Hasil penelitian ini menunjukkan: pertama, nilai-nilai esensial dari filantropi dalam pendidikan Islam yang digunakan pada pesantren Dalwa bersumber dari teks agama dan panggilan kemanusiaan. Kedua, bentuk program-program filantropi dalam pendidikan Islam yang diimplementasikan pada pesantren Dalwa terdapat tiga bentuk yaitu filantropi pada Santri, Masyarakat, Guru dan Asatidz. Ketiga, Ideologi yang menjadi landasan dalam mengkonstruksi filantropi pendidikan Islam yang dimiliki pesantren dalwa yaitu hibrida keilmuan: á¸¥aá¸ramiyah dan makiyah serta ideologi filantropi yang mengarah pada ketidakafiliasian dengan organisasi Islam. Kata Kunci: Filantropi, Pendidikan Islam, Pesantren